Offshoring, labor market mobility and wage growth - Antti Kauhanen (The Research Institute of the Finnish Economy (ETLA), 2013)
Abstract:This paper uses longitudinal linked employer-employee data to study how firms' offshoring decisions affect labor market mobility and the wage growth of their employees. The results show that offshoring affects mobility primarily in occupations that are easily offshored. Wage growth, however, is weaker in the occupations that are offshorable, even if the employer has not offshored, and for employees whose initial employer has offshored some activities, irrespective of their occupation
Keywords: 330; wages; job mobility; linked employer-employee data; unemployment